2019
DOI: 10.2478/popets-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

4 Years of EU Cookie Law: Results and Lessons Learned

Abstract: Personalized advertisement has changed the web. It lets websites monetize the content they offer. The downside is the continuous collection of personal information with significant threats to personal privacy. In 2002, the European Union (EU) introduced a first set of regulations on the use of online tracking technologies. It aimed, among other things, to make online tracking mechanisms explicit to increase privacy awareness among users. Amended in 2009, the EU Directive mandates websites to ask for informed c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 21 publications
4
40
0
Order By: Relevance
“…Various studies have tried to chart the impact of European privacy regulation on the collection and processing of personal data on the web, both within its territorial scope and globally. A longitudinal 4-year study of the impact of the revised ePrivacy directive on cookie placement shows that 1) 49% of websites placed cookies before receiving consent; 2) 28% of websites did not provide any consent mechanism; and 3) the percentage of websites violating the directive stayed constant over the course of 4 years, indicating the policy to be ineffective [48].…”
Section: Empirical Studies Of Eu Privacy Regulationmentioning
confidence: 99%
“…Various studies have tried to chart the impact of European privacy regulation on the collection and processing of personal data on the web, both within its territorial scope and globally. A longitudinal 4-year study of the impact of the revised ePrivacy directive on cookie placement shows that 1) 49% of websites placed cookies before receiving consent; 2) 28% of websites did not provide any consent mechanism; and 3) the percentage of websites violating the directive stayed constant over the course of 4 years, indicating the policy to be ineffective [48].…”
Section: Empirical Studies Of Eu Privacy Regulationmentioning
confidence: 99%
“…All construct items are reported in Table 1. Answers were collected on 5point rating scales with semantic anchors "strongly disagree" (1) and "strongly agree" (5). Perceived deception (PDE) is assessed using three (of originally four) items by Román [44], adapted to the context of our study.…”
Section: Pde2mentioning
confidence: 99%
“…6.3 below). However, our choice of stimulus was not driven by the most prevalent design, which we and other researchers [5,9,10] suspect to trivially violate the GDPR. Instead, we set out to study elementary design options of multi-purpose dialogs, the novel and most under-researched aspect of consent dialogs.…”
Section: Validity and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2000, disclosure towards the users about cookie usage has increased (Miyazaki, 2008), and we can say that the GDPR regulation that came in 2018 was a natural continuity of this trend of transparency on how personal data is used on the internet. User's rights to privacy is not necessarily a value for the most websites, as in 2017, in Europe, 49% of them did not respect the European Union Directive that introduced a first set of regulations in 2002 (Trevisan, Traverso, Bassi & Mellia 2019). A study regarding the GDPR cookie consent compliance found out that 54% of the websites violate in a way or another the GDPR regulation (Matte, Bielova & Santos, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%